2015
DOI: 10.1111/hsc.12244
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing food allergy status in schools: health-related stigma among school children in Ontario

Abstract: In 2006, 3 years after the tragic death of 13-year-old Sabrina Shannon, the Province of Ontario (Canada) passed Sabrina's Law ushering in a new era of focus and concern for severe food allergic children at risk of anaphylaxis. Questions were raised at the time regarding the potential of doing more harm than good with the new legislation. This paper reports the experiences of health-related stigma among food allergic children at risk of anaphylaxis who were required to disclose their health status under this ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 63 publications
3
77
0
Order By: Relevance
“…, Dean et al . ). The adolescents in our study had experienced school trip to restaurants where they could not tolerate the food as, for example, peanuts are common ingredients of Asian, Chinese and Mexican cookery.…”
Section: Discussionmentioning
confidence: 97%
“…, Dean et al . ). The adolescents in our study had experienced school trip to restaurants where they could not tolerate the food as, for example, peanuts are common ingredients of Asian, Chinese and Mexican cookery.…”
Section: Discussionmentioning
confidence: 97%
“…The third synthesis shows teens are enmeshed in social and political contexts that affect their experiences living with FIA. One excluded study from Ontario, Canada described the unintended effects of a school policy requiring disclosure of allergies in students: despite normalizing FIA, it also labelled students, making them subject to bullying and stigma (Dean et al., ). The policy thus highlighted how the artificial divide between physical/medical health and social health creates conflict, reflecting the central struggle in our review that many teens faced in managing perceived risks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified particular groups who are more concerned than others, namely, females, older adults, recent immigrants to Canada, and those with lower levels of education [1]. Others have examined the management and experience of risks from the perspective of food allergic children [3, 4] and adolescents [5] and other vulnerable populations including low income families [6] and recent immigrants [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Following the enactment of Sabrina's Law [15] in 2006, all publicly funded elementary and secondary schools in Ontario are mandated to train and educate staff about the risks of allergic reactions and are accountable for the management of pupils with severe (i.e., anaphylactic) allergies. However, there is evidence to suggest that while fatal allergic reactions do occur in schools [16], policies are more lenient in high schools in comparison with elementary schools [4] and that there is a relative paucity of support for food allergic individuals at the postsecondary level [17]. The result is that youth and young adults are interacting with foods in increasingly risky places with respect to the control of allergens and treatment of allergic reactions.…”
Section: Introductionmentioning
confidence: 99%